BELLY DEPTH STUDIES FOR SHRIMP TRAWLS-PART III - MHALATHKAR, H N; JEGADEESAN, G (Fishery Technology, 2025)
Earlier investigations with 13.69 m ( 45’) four seam shrimp trawl indicated the optimum depth of belly to be 70 meshes. Present communication details further experiments on similar lines with a bigger shrimp trawl of size 17.07 m (56’) without overhang. The resu]ts obtained have not only given corroborating evidence in support of the earlier findings but also helped in arriving at a relationship that for a given stretched width of belly ’L’ the stretched depth of beUy could be either 2L/5 or 40% of â€¢L’ with an allowance of Â± 2 meshes.